Evaluating an 'incident control' approach to non-communicable disease. (August 2021) - Horsley, S.M.; Morling, J.R.; Khaw, F.M.; Day, M.
Abstract: Objectives: This article evaluates the application of 'incident control' methodology usually applied in communicable disease control to an 'incident' of unexplained deaths, specifically to resolve a significant difference in 1-year survival after a lung cancer diagnosis observed between two Clinical Commissioning Groups and the England national average, 2011–14. The purpose of the evaluation was to assess whether a formalised incident control approach is feasible and effective in improving outcomes for non-communicable diseases. Study design: Descriptive, qualitative, process evaluation. Methods: There were two components to the evaluation: a document review against identified phases of a non-communicable disease incident control framework and a qualitative analysis of semi-structured interviews with stakeholders who had been involved in implementation. Results: The findings indicate feasibility of the incident control model, with some limitations. Identified strengths of the model included the articulation of a clear case and incident definition. The structure and stepped phased approach facilitated partner engagement, robust data analysis, action planning and communication strategies. Delays in data publication and the lack of comparable data across different non-communicable diseases present challenges in timely response and prioritisation of 'incidents'. Conclusions: The evaluation indicates value in applying defined incident control methodology to management of non-communicable diseases, especially where there is identification of a potential outlier or a measurable variation, i.e. there is a definable 'incident' and 'case'.